Urban Existence in the Interwar English Literature - Devdiuk, Ivanna (Respectus Philologicus, 2019)
The paper highlights the peculiarities of the artistic modifications of urban existence in the English literature of the interwar period. We have analysed such novels as Death of a Hero by Richard Aldington, Antic Hay by Aldous Huxley, and Mrs. Dalloway by Virginia Woolf, in which in the light of M. Heidegger’s analytic of Dasein, we investigated the ways of the main characters’ awareness of their own possibilities in a city. The article follows through the correlation between the heroes’ existence and urban reality, in which it is projected. We have discovered that in the novels Death of a Hero and Antic Hay urban discourse is characterised by eschatological markers, in which the semantics of the heroes’ loss of spiritual values and beliefs is expressed. Because of the lack of understanding of the world, George Winterbourne and Theodore Gumbrill are not capable to perceive true nature of their own selves and achieve maturity. This leads to self-alienation and dissolving in the ‘they’, which is a manifestation of falling into average everydayness. The mode of pr ojection of oneself into the future is illustrated by the image of Mrs. Dalloway from the eponymous novel by Virginia Woolf, in which the horizon of existence is revealed as a free choice in the face of finitude. The study demonstrates how differently characters can perceive the city in the face of a choice between true and untrue existence, between themselves and others, between freedom and dependence.
Keywords: urban; existence; mode; authenticity; thrownness